Devastating impact of ruptured ectopic pregnancy - Jhirwal, Manisha; Bohra, Deepika; Singh, Pratibha (International Journal of Research in Medical Sciences, 2024)
An ectopic pregnancy is a condition in which fertilized ovum implants and develops outside normal uterine cavity. Most common site for ectopic pregnancy is fallopian tube (95%). The incidence of ectopic pregnancy ranges 1-2% in India, the most common reason being artificial reproductive technology accounting for 2-5% in patients. There are marked differences in the mortality ratios around the globe, with none mortality to 3.5%. Clinical presentation of ectopic pregnancy may mimic the intrauterine pregnancy with some of the same symptoms such as a missed menstrual period, vaginal bleeding, low back pain, mild pain in the abdomen or pelvis. Value of beta- human chorionic gonadotropin (HCG) >1500 u/l with no intrauterine pregnancy on transvaginal scan is almost confirmatory of ectopic pregnancy.